Field DCP testing, MSEW analysis, and monitoring-based investigation of a reinforced earth retaining wall collapse - Minwoo Kim (PLoS ONE, 2025)
Reinforced retaining walls are critical components of urban infrastructure, yet failures continue to occur due to complex geotechnical and environmental factors. This study investigates a collapse case, focusing on the influence of water infiltration from a damaged sewage pipe near a manhole. Photo documentation and portable dynamic cone penetration (DCP) testing were conducted to evaluate subgrade strength and identify localized weaknesses. Results revealed significant variability in ground rigidity, with particularly low resistance values near the manhole, indicating deterioration caused by seepage and soil softening. Stability analysis using MSEW software, under both static and seismic conditions, confirmed that affected wall sections did not meet safety requirements. Based on these findings, targeted remediation measures are proposed, including soil nailing, low-pressure grouting, and embankment reinforcement, complemented by continuous monitoring using displacement targets and inclinometers. This integrated approach offers both diagnostic insight and practical strategies to improve the design, maintenance, and resilience of MSE retaining walls, providing valuable guidance for engineers and decision-makers in preventing similar failures in densely built urban environments.